STUDY ON THE INHIBITORY EFFECT OF DRYNARIA FORTUNEI EXTRACT ON HUMAN MYELOMA SP20 CELLS - Li, Baofeng; Duan, Tingting; Fan, Lei (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of the study was to investigate the inhibitory effect of Drynaria fortunei extract on human myeloma SP2 cells. Three different total extracts of Drynaria fortunei were obtained by reflux extraction method using different organic solvents including ethanol, methanol and petroleum ether. Their anticancer activities on SP20 cells were tested, and the maximum inhibition rate was obtained. The inhibitory effects on tumour cells at 12 h, 24 h, 36 h and 48 h were tested, and the inhibition curves at different time periods were plotted. The results showed that the methanol and ethanol extracts have similar inhibition rates at 24 h, which are around 55%. On the other hand, the maximum inhibition rate of petroleum ether extract is only 36% within 24h. Moreover, within the time periods of 36 h and 48 h, its inhibition rates are all below 10%.